Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s40104-022-00770-8
|View full text |Cite
|
Sign up to set email alerts
|

Restored intestinal integrity, nutrients transporters, energy metabolism, antioxidative capacity and decreased harmful microbiota were associated with IUGR piglet's catch-up growth before weanling

Abstract: Background Intrauterine growth restriction (IUGR) is a major inducer of higher morbidity and mortality in the pig industry and catch-up growth (CUG) before weanling could significantly restore this negative influence. But there was limited knowledge about the underlying mechanism of CUG occurrence. Methods Eighty litters of newborn piglets were divided into normal birth weight (NBW) and IUGR groups according to birth weight. At 26 d, those piglets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Finally, these samples were stored at −80 °C until further analysis. The intrauterine growth restriction (IUGR) piglets are defined as the average birth weight minus 2 standard errors . In this experiment, the mean birth weight of the 874 piglets was 1.42 ± 0.20 kg (mean ± standard error), so piglets with a birth weight of less than 1.02 kg (1.42 – 0.40) were defined as IUGR piglets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, these samples were stored at −80 °C until further analysis. The intrauterine growth restriction (IUGR) piglets are defined as the average birth weight minus 2 standard errors . In this experiment, the mean birth weight of the 874 piglets was 1.42 ± 0.20 kg (mean ± standard error), so piglets with a birth weight of less than 1.02 kg (1.42 – 0.40) were defined as IUGR piglets.…”
Section: Methodsmentioning
confidence: 99%
“…The intrauterine growth restriction (IUGR) piglets are defined as the average birth weight minus 2 standard errors. 18 In this experiment, the mean birth weight of the 874 piglets was 1.42 ± 0.20 kg (mean ± standard error), so piglets with a birth weight of less than 1.02 kg (1.42 − 0.40) were defined as IUGR piglets. Moreover, when counting the proportion of IUGR piglets, sows were categorized into two classes based on the average number of piglets born alive per litter (15.0 piglets): low-yield sow (the number of piglets born alive <15.0) and high-yield sow (the number of piglets born alive ≥15.0).…”
Section: ■ Introductionmentioning
confidence: 92%
“…However, our results showed that the long-term adverse effects persisted in barrier function and a lessened disparity in TJs proteins between the NBW and IUGR pigs, which might be associated with the catch-up growth. Another study revealed that IUGR piglets with a catch-up growth before weaning exhibited a recovered intestinal physical barrier, including occludin, claudins, and ZO-1, almost as good as NBW piglets [ 31 ]. The “thrifty phenotype” hypothesis suggests that when nutritional conditions in the uterus are suboptimal, metabolism and growth of the fetus are restricted; but when the postnatal nutritional condition is adequate, IUGR pigs undergo a catch-up growth, such a process is likely resulting from an adaptive process in adverse conditions [ 1 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher microbial diversity tends to indicate that the host has greater disease resistance. Previous studies have shown that piglets with higher α-diversity have lower inflammatory factor levels and a greater antioxidant capacity in the intestine, and the protein expression levels of ZO-1, occludin, and claudin-1 are also higher ( 37 ). Furthermore, α-diversity is associated with feed efficiency ( 38 ).…”
Section: Discussionmentioning
confidence: 99%